Estimating the technical feasibility of fuel cell and battery electric vehicles for the medium and heavy duty sectors in California. (15th October 2020) - Forrest, Kate; Mac Kinnon, Michael; Tarroja, Brian; Samuelsen, Scott
Graphical abstract: Highlights: A representative model of medium and heavy duty trips in California is presented. Medium and heavy duty battery electric vehicle charging profiles are developed. Electric vehicle potential to meet medium and heavy duty trips is quantified. Uncertainty around future fuel efficiency and charging infrastructure is discussed. Abstract: Transitioning the medium and heavy-duty vehicle fleet to electric vehicles (EVs) such as battery electric vehicles (BEVs) and fuel cell electric vehicles (FCEVs) is an important step in supporting greenhouse gas and regional air pollutant emission reduction goals. Travel demand patterns for medium and heavy-duty vehicles, however, have a more diverse and stricter set of requirements compared to light duty vehicles. Therefore, it is critical to understand the technical feasibility of using BEVs and FCEVs to meet the medium and heavy duty vehicle travel demands as a function of vehicle capabilities and infrastructure availability. This work develops and applies a representative dataset of California-based medium and heavy duty vehicles trips to evaluate (1) potential electric load demand of future BEVs and (2) the feasibility of EVs to meet state-wide medium and heavy duty travel demand. From a technical perspective, EVs can support between 62 and 76% of commercial Class 2B-7 vehicle miles traveled with technologies in development today. Further increases will require increasing vehicle range, improving fuel efficiency, and/or expanding available charging locations. Class 8 trucks have a much lower BEV feasibility compared to FCEVs due to their weight and longer trip distances, with 100-mile vehicles meeting up to 8% of vehicle miles travelled with home base charging. Class 8 FCEVs with the same range can meet up to 27% and are likely to have expanded ranges that facilitate up to 68% due to inherent benefits of storing on-board hydrogen relative to batteries. Feasibility results indicate that EVs can significantly contribute to reducing emissions from the medium and heavy duty sectors but cannot fully meet demand under the configurations considered.